The Coach Leadership Style: How it Impacts on the Sports Commitment and Playing Skills of Student Tennis Athletes? - Setiyo Hartoto; Mochamad Ridwan; Dony Andrijanto; Joesoef Roepajadi; Muhamad Asrul Sidik; Armando Monterrosa-Quintero; Dan Iulian Alexe; Dragos Ioan Tohanean; Edi Setiawan (OVS LLC, 2023)
Study purpose. The objective of this study was to investigate the effect of the coach's leadership style model on increasing the level of sports commitment and tennis skills. Materials and methods. A mixed method was applied in this study. The participants (n=30) were student athletes at Surabaya State University. This study used the quantitative instrument which used the sports commitment grade scale to assess the level of sports commitment, the forehand and backhand tests were used to measure playing skills. While the qualitative instrument used in-depth interviews. The independent sample t-test was used to present differences in sports commitment scores and playing skills before and after the experiment in the experimental and control groups. The paired sample t-test was used to evaluate the effect of the coach's leadership style model on the experimental and control groups. Qualitative statistical analysis used qualitative thematic analysis. Results. The quantitative study results showed that there was no difference in the level of sports commitment and playing skills between the experimental and control groups before the experiment (p>0.05), but there was a difference after the experiment (p<0.05). The paired sample t-test proved that the effect on increasing sports commitment and playing skills in the experimental group was better than in the control group (p<0.05). In qualitative research, student athletes stated that the coach's leadership style had advantages and disadvantages. Conclusions. Finally, student athletes emphasized that this program had a real and positive impact on the development of their sports commitment and playing skills.